Testing the Efficiency of Zinc Oxide Nanoparticles, Honey, Honey Supported by Zinc Oxide Nanoparticles and Phylex in Degradation of Aflatoxin B1 in stored Sea Maize Seeds - Dema A Yousif (Journal of Global Pharma Technology, 2019)
This study was conducted at the Mycotoxins Laboratory/ Department of Plant Protection /College of Agriculture/ University of Baghdad to test the efficacy of zinc oxide nanoparticles (ZnO (NP)), honey, honey supported by zinc oxide nanoparticles and Phylex in inhibition of Aspergillus flavus and degradation the toxin that produced by the fungus. The efficacy of ZnO(NP) was tested with concentration 2% and honey with concentration 20% and honey supported by ZnO(NP) with 20% concentration and the Phylex 0.2% under storage conditions. The results indicated that all treatment resulted a significant decline in the reduction rate and concentration of Aflatoxin B1 (AFB1) in stored Sea maize seeds with a significant difference from control treatment, which was 0.0 and 1.13 μg/kg by using high performance liquid chromatography (HPLC). As for choosing best concentration for each of the materials used to inhibit fungus growth, the results showed the used of ZnO(NP) and the Phylex have the highest reduction rate. This rate in Aflatoxin B1 was 93.80% with a concentration of 0.07 μ/kg and 91.15% with a concentration of 0.10 μg/kg respectively. The results of using honey showed the reduction rate of Aflatoxin B1 79.64% with a concentration of 0.23 μ/kg. Then was followed by the use of honey supported by ZnO(NP) with a reduction rate of Aflatoxin B1 82.30% and concentration 0.20 μg/kg. The results showed the efficacy of ZnO (NP), honey and honey supported by ZnO(NP) and Phylex in degradation A. flavus and prevent producing of Aflatoxin B1 in Sea maize seeds in compression of control treatment that was 1.12 μg/kg using HPLC device. It was found when using ZnO(NP) reduction rate of Aflatoxin B1 was 96.42% with concentration of 0.04 μg/kg, while the rate of Aflatoxin B1 reduction was 72.32% at a concentration of 0.31 μg/kg when using honey. The results of the use of honey supported by ZnO(NP) indicated a rate of reduction Aflatoxin B1 was 83.92% B1 with a concentration of 0.18 μg/kg, the results of the use of the Phylex showed the reduction rate of Aflatoxin B1 was 94.64% with a concentration of 0.06 μg/kg.Keywords: Aflatoxin B1, ZnO(NP), Phylex, honey, Inhibition, Aspergillus flavus.